Modeling Transportation Mode Choice Using the Multinomial Logit (MNL) Model in the City of Kotamobagu - Rendy Lodewiyk Suwu; Lucia Ingrid Regina Lefrandt; Joice Waani (PT Publikasiku Academic Solution, 2026)
This research aims to analyze the factors affecting transportation mode choice in Kotamobagu City, measure the influence of travelers’ socioeconomic characteristics, and determine the probability of choosing among motorcycles, private cars, and bentor (motorized three-wheeled vehicles). The research employed a quantitative descriptive method using a survey approach conducted across four sub-districts. Primary data were collected through questionnaires administered to 153 respondents and analyzed using the Multinomial Logit Model (MNL) in SPSS. The results of the simultaneous tests showed that all independent variables examined (cost, safety, travel time, and convenience considerations) significantly contributed to transportation mode choice decisions. However, based on partial tests, three main factors were found to be the most dominant and statistically significant, namely gender, travel destination, and the reasons for choosing a mode, particularly cost and travel time considerations. Male travelers and those traveling for work-related purposes demonstrated a higher tendency to choose motorcycles. Meanwhile, segments such as housewives, students, and civil servants showed a stronger preference for bentor compared with motorcycles. The final results of the modeling indicate that mobility preferences in Kotamobagu City are highly dominated by private vehicles, with a combined market share of 94%. Motorcycles and private cars are the two most dominant modes, with choice probabilities of 47.64% and 46.36%, respectively. In contrast, bentor occupies the lowest position, with a choice probability of only 6.00%. These findings indicate that bentor remains a secondary transportation option, primarily serving specific passenger segments or particular travel needs in Kotamobagu City.